Cara Sukses Generasi Muda dalam Berwirausaha - Yusuf Suhardi; Meita Pragiwani; Zulkarnaini Zulkarnaini; Arya Darmawan; Sri Handoko Sakti; Irfan Arif Husen (LPMP Imperium, 2025)
Vocational high school (SMK) students, as part of the younger generation with strong physical and mental potential, must be equipped with productive knowledge to become independent and not a burden to their families or the government. This community engagement activity focused on developing an entrepreneurial mindset by presenting successful and failed business case studies and strategies to build and sustain a business. The activity used interactive methods: lectures, discussions, and Q&A sessions. These approaches created an engaging learning environment, encouraging students to ask questions and explore business topics more deeply. Lecturers from STIE Indonesia delivered contemporary business case studies, making the sessions relevant and intellectually engaging. Held on Tuesday, March 18, 2025, at SMK Tunas Markatin, Jakarta, the program resulted in high student enthusiasm and understanding of entrepreneurship. Students showed interest in generating creative business ideas and recognized the importance of business planning connected to their school subjects in economics and entrepreneurship. Success indicators included active participation during discussions, students’ ability to create basic business plans, and the school’s commitment to guiding students in continuing entrepreneurship development.